Artificial neural networks model for predicting the behavior of different injection pressure characteristics powered by blend of biofuel‐nano emulsion. Issue 7 (7th April 2022) - Elumalai, P. V.; Krishna Moorthy, R.; Parthasarathy, M.; Samuel, Olusegun David; Owamah, Hilary I.; Saleel, C Ahamed; Enweremadu, Christopher C.; Sreenivasa Reddy, M.; Afzal, Asif
Abstract: This investigation deals with the usage of graphene oxide (GO) nanoparticles with orange peel biodiesel in a conventional CI engine. The different fuel blends used for this experiment are biodiesel 10% + diesel 80% + ethanol 5% + surfactant 5% + GO 50 ppm (B10), biodiesel 20% + diesel 70% + ethanol 5% + surfactant 5% + GO 50 ppm (B20), biodiesel 50% + diesel 40% + ethanol 5% + surfactant 5% + GO 50 ppm (B50) and B100. The addition of ethanol has dual benefits for improving the vaporization of fuel blends and reduction of oxides of nitrogen (NOx) emission. Span80 and Tween80 were chosen as surfactants based on hydrophilic‐lipophilic balance numbers. It is useful for improving the homogeneity of immiscible fuel blends. From this study, the injection pressure (IP) was varied from 180, 200 to 220 bar for better atomization characteristics of nano additive biodiesel blend. The experimental results indicated that an increase in the percentages of biodiesel beyond 20% in the blend, NOx increases, and hydrocarbon (HC) and carbon dioxide (CO) emissions were found to be decreased. It is also observed that the highest brake thermal efficiency (BTE) was found for fuel 20 at the IP of 220 bar. The addition of nano additive has a great influence on fuel droplets and reduction of NOx emission levels. B20 blend was found to higher cylinder pressure and heat release rate when compared to other nano additive blends. Finally, indicated that the nano additive B20 blend is a better alternative to conventional fuel in unmodified CI engines. The RMSE value for the BTE, brake‐specific energy consumption (BSEC), CO, HC, NOx, and smoke is obtained to be 0.036, 0.0216, 0.044, 0.041, 0.0446, and 0.0435, respectively. The mean absolute percentage error value for the BTE, BSEC, CO, HC, NOx, and smoke is obtained to be 1.12, 0.84, 3.04, 4.12, 1.71, and 0.97, respectively. Abstract : Usage of graphene oxide (GO) nanoparticles with orange peel biodiesel in a conventional CI engine is reported. The different fuel blends used for this experiment are biodiesel 10% + diesel 80% + ethanol 5% + surfactant 5% + GO 50 ppm (B10), biodiesel 20% + diesel 70% + ethanol 5% + surfactant 5% + GO 50 ppm (B20), biodiesel 50% + diesel 40% + ethanol 5% + surfactant 5% + GO 50 ppm (B50) and B100. The addition of ethanol has dual benefits for improving the vaporization of fuel blends and reduction of oxides of nitrogen emission.